Kurikulum Merdeka: Meningkatkan Kualitas Pembelajaran dengan Kebebasan dan Fleksibilitas - Koni Olive Tunas; Richard Daniel Herdi Pangkey (Departement of Mathematics Education, 2024)
How the implementation of Independent curriculum in improving the quality of learning with freedom and flexibility. The implementation of The Independent curriculum has brought significant changes in improving the quality of learning in Indonesia. This curriculum gives teachers, students and the community the freedom and comfort to create more innovative and creative content and learning methods. The curriculum must follow the essence and character of the Times and pay attention to the diversity and inclusiveness of the teaching and learning process. The Independent curriculum gives students the opportunity to get more meaningful and personalized learning. The purpose of this study to determine the concept of independent curriculum as an aspect of learning with freedom and flexibility. In this study using the type of qualitative research, using the method of literature study. The technique of collecting data in this study is by searching in electronic books (e book) and the latest scientific articles: looking for information in catalogs and library databases. With the aim of solving the problem by tracing the sources of writing that have been made before that are in line with the title of this study.